Implementation of Karate Values to Shape The Character of Karate Extracurricular Participants - Rama Shinta Safmelita; Syahrial Bakhtiar; Yendrizal; Alnedral (Universitas Negeri Semarang, 2024)
This study aims to evaluate the improvement of the character of karate extracurricular participants through the implementation of karate values in the activity, as well as to compare differences in children's character before and after participating in training for 3 months. The research method used is qualitative with data collection through interviews, observation, and documentation, and the validity of the data is tested by triangulation. The results showed that the application of karate values was successful in shaping the character of extracurricular participants. Training ceremonies, discipline, and playtime activities are well integrated, making the child happy and not bored. Karate vows also have a positive impact, such as increased personality, honesty, fighting power, ethics, and self-control. The implementation of the first karate vow succeeded in improving the child's personality by increasing social interaction and mutual respect. Although character still needs to be improved, character education through karate helps parents in imparting positive values to children. The second karate vow, which emphasizes honesty, is reflected in the child's courage to admit his mistakes. While the third to fifth karate vows, which emphasize achievement, courtesy, and self-control, are also successfully applied and improve the child's character in a better direction. Thus, this study concluded that the implementation of karate values in extracurricular exercises is able to shape children's character, including aspects of personality, honesty, fighting power, ethics, and self-control.